The Impact of the Discovery Learning Model on Problem-Solving Ability and Scientific Attitude of Elementary School Teacher Education Students - Ananda, Puspita Dwi; Haryanto; Atmojo, Setyo Eko (Universitas Pendidikan Ganesha, 2022)
The abilities or skills that should be possessed in science learning have become less than optimal due to the Covid-19 pandemic. This study aims to analyze the effect of the application of the Discovery Learning model on the problem-solving abilities and scientific attitudes of elementary school teacher education students in science learning. This type of research is quasi-experimental with a non-equivalent control group design. The population used in this study were students of the even semester Elementary School Teacher Education Study Program, totaling 78 students and collecting data using the test method, with instruments in the form of test questions in the form of essay tests to test problem-solving skills and observation sheets to determine scientific attitudes. The data analysis technique used descriptive, normality, homogeneity, hypothesis, and Manova tests. The results showed that the average score of the scientific attitude of the experimental class students was higher than the average score for problem-solving skills and the average score of the control class. Thus, it can be concluded that the Discovery Learning model influences problem-solving abilities and scientific attitudes of elementary school teacher education students in science learning.